Junge Szene '96. - Quinn, Jonathan; Rothauer, Doris; Sellitsch, Siegfreid; Spiegl, Andreas (Wien : Wiener Secession, 1996)
The audioroom ; Artophobia ; Brasilica ; etoy ; Büro Josef Böhm ; Die Fabrikanten ; Fond ; Gelatin ; Hübner, Herbert ; G.R.A.M. ; H.A.P.P.Y. ; Heger/Dejanov ; Hilus ; Kommunikationsradio & Christof Cargnelli & Peter Szely ; Public Netbase ; Quinn, Jonathan ; Trabant featuring Christoph Hinterhuber
Junge Szene 1996, Wiener Secession, Wien, 19.7. - 15.9.1996
Duits & Engels
kunstcatalogus